2004
DOI: 10.1002/mop.20156
|View full text |Cite
|
Sign up to set email alerts
|

Load matching in multimode microwave‐heating applicators based on the use of dielectric‐layer moulding with commercial materials

Abstract: Commercial dielectric materials placed around a sample are studied as load‐matching elements for multimode microwave‐heating applicators. The dimensions of these dielectric materials are optimized with an iterative procedure in order to achieve high‐power efficiency, thus enhancing electric‐field deposition within the sample. © 2004 Wiley Periodicals, Inc. Microwave Opt Technol Lett 41: 414–417, 2004; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.20156

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…However, it is rather difficult to design an appropriate system according to the material which will be heated in spite of the present numerical methods, and very few studies have been carried out in this field [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is rather difficult to design an appropriate system according to the material which will be heated in spite of the present numerical methods, and very few studies have been carried out in this field [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Common problems of all those methods are the high sensibility 2 to the variation of the dielectric properties, and shape and dimensions of the sample to be heated. Other authors have shown that it is possible to achieve high power efficiencies by using dielectric casts around the sample [3,4]. However, these methods have not been experimentally tested yet, showing only simulated data.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods have tried to optimize the efficiency of microwave heating devices from an electromagnetic point of view [5]- [6], although these methods are very slow mainly due to the high computational cost for each iteration during the optimization loop. Other problems from the classical methods, including mechanical elements, are related to the use of irises and waveguide tuning screws acting as triple or quadruple stubs [1,2], which need to be finely tuned to provide an adequate match to load and frequency conditions.…”
Section: Introductionmentioning
confidence: 99%
“…sample, achieving 24 low reflections back to the magnetron and maximum power transfer to the sample [2]. Other authors have shown that it 25 is possible to achieve high power efficiencies by using dielectrics around the sample [3,4] or by placing the material to 26 be heated at an optimal position for which the reflection coefficient at the feeding port is minimized [5]. However, all of 27 these devices and methods used for increasing power efficiency are based on the minimization of the so-called 28 reflection coefficient at the feeding port mainly at 2.45 GHz which is the central frequency of the corresponding 2.4- assumed frequency and that, in fact, the spectrum of the magnetron varies with internal temperature, aging, 32 manufacturer model, power reflections and output power.…”
mentioning
confidence: 99%
“…However, all of 27 these devices and methods used for increasing power efficiency are based on the minimization of the so-called 28 reflection coefficient at the feeding port mainly at 2.45 GHz which is the central frequency of the corresponding 2.4- assumed frequency and that, in fact, the spectrum of the magnetron varies with internal temperature, aging, 32 manufacturer model, power reflections and output power. As a result, it seems very difficult to know a priori the output 33 frequency of any magnetron which makes the adapting devices and procedures described in [1][2][3][4][5] difficult to be 34 implemented with guaranties for all magnetron producers or models.…”
mentioning
confidence: 99%